Efficacy of natural killer T and gammadelta T cells in mesothelin-targeted immunotherapy of pancreatic cancer - Yuankui Zhu; Yaxi Yang; Linghe Yue; Lei Wan; Xuqian Ma; Qing Yang; Xuan Tian; Yuguan Li; Ke Wang; Shaozhong Wei; Shaozhong Wei; Shaozhong Wei; et al. (Frontiers in Immunology)
Current pancreatic cancer immunotherapy focused on alphabeta (αβ) T cells, either through CD3-engaged bispecific antibodies or CAR-T. Despite their promise, dose-limited toxicity (DLT) remains a challenge in clinical practice. In light of these concerns, there is a growing interest in exploring alternative T cell types, natural killer T (NKT) cells and gammadelta (γδ) T cells, that possess the capacity to lyse tumors while potentially offering a safer therapeutic profile with fewer side effects. These cells present a compelling alternative that warrants a comprehensive evaluation of their therapeutic potential and safety profile. This study employed a MSLN/CD3 bispecific antibody to compare the anti-tumor activity of NKT and γδT cells with peripheral blood mononuclear cells (PBMCs) as controls, both in vitro and in vivo. This study demonstrated that MSLN/CD3 BsAb effectively activated and recruited PBMCs, NKT and γδT. Furthermore, under the influence of MSLN/CD3 BsAb, γδT and NKT cells exhibited notably superior anti-tumor activity compared to PBMCs, both in vitro and in vivo, while demonstrating low cytokine release. γδT cells showed almost negligible toxic side effects. In addition, the systemic administration of NKT and γδT cells activators, α-galactosylceramide (α-GalCer) and Zoledronate, could enhance the anti-tumor effect of MSLN/CD3 bsAb, with no apparent toxicity. NKT and γδT cells are promising synergistic therapeutic cell types that may overcome the limitations of CD3 bispecific antibodies in pancreatic tumor treatments, offering a new perspective for clinical applications in immunotherapy.